A new approach for longitudinal vibration of a large-diameter floating pipe pile in visco-elastic soil considering the three-dimensional wave effects. (December 2020) - Meng, Kun; Cui, Chunyi; Liang, Zhimeng; Li, Haijiang; Pei, Huafu
Abstract: A novel approach is presented to describe the dynamic interaction system of a large-diameter floating pipe pile and surrounding soils, taking the three-dimensional wave effects into account. The corresponding analytical solutions for longitudinal complex impedance are obtained and subsequently validated via comparisons with existing solutions. Comparative analyses are also performed to illustrate the difference between the present and previous solutions, concerning the wave propagation effect in the radial direction on the longitudinal dynamic vibration of pile shaft. Furthermore, the effects of Poisson's ratio and visco-elastic support beneath the pile toe, on the longitudinal dynamic vibration of pile shaft, are investigated. It is indicated that the presented approach and corresponding solutions provide a more wide-ranging application for longitudinal vibration analysis of a large-diameter floating pipe pile, which can also be reduced to analyze the longitudinal vibration problems of large-diameter floating solid pile and fixed- end pipe pile.